(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: This study aimed to evaluate the impact of an experiential learning intervention among middle school teens by midwifery students to reduce the risk of teen pregnancy. Methods: This research was a controlled pre-and post-test design study aimed to evaluate the impact of experiential learning intervention “Smart Teens Program” among middle school students. The data on knowledge, attitude, and subjective norms were collected during a pre-test and posttest (six weeks for intervention), in a control group (n=70) and an intervention group (n=68). The data were collected from self-administered questionnaires and analyzed using STATA (version 12.0). Results: The results showed a significant impact of the intervention “Smart Teen Program” by midwifery students, where there was a significant increase in the knowledge, attitude, and subjective norms in reducing the risk factors of teen pregnancy (p-value = 0.00). The control group who was not given any treatment showed a decreased value. Conclusions: Interventions through experiential learning by midwifery students were able to improve efforts to prevent teen pregnancy. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 797-803